Ultra-wideband electromagnetic shielding and bulletproof composite structure material and preparation method thereof

By using ultra-wideband electromagnetic shielding and bulletproof composite structural materials, including wave-transparent skin, aramid honeycomb sandwich, reflective plate and bulletproof back plate, the problem of poor absorption effect of existing electromagnetic shielding materials in the high frequency band is solved, and excellent electromagnetic shielding effect and protective performance in the range of 1 to 45GHz is achieved, while reducing production costs and simplifying the process.

CN119677075APending Publication Date: 2025-03-21BEIJING AEROSPACE KAIEN NEW & ADVANCED MATERIAL CO LTD +2

Patent Information

Application Number
CN202411692804.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials have poor absorption effects in higher frequency bands, and are highly prepared, complex in process, and do not have protective performance.

Method used

An ultra-wideband electromagnetic shielding and bulletproof composite structural material is adopted, including wave-transparent skin, aramid honeycomb sandwich, reflector plate and bulletproof back plate, and the structural module is bonded through modified resin adhesive to achieve composite.

Benefits of technology

It significantly improves electromagnetic shielding efficiency, has excellent electromagnetic shielding effect in the ultra-wide band of 1 to 45GHz, and has protective performance, reducing production costs and simplifying the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677075A_ABST
    Figure CN119677075A_ABST
Patent Text Reader

Abstract

The invention provides an ultra-wideband electromagnetic shielding and bulletproof composite structure material and a preparation method thereof, and belongs to the field of preparation of electromagnetic wave-absorbing materials. The invention aims to solve the problems that the current electromagnetic shielding material is narrow in absorption wave band, the composite structure material is high in preparation cost and complex in process, and does not have protection performance. The ultra-wideband electromagnetic shielding and bulletproof composite structural material is mainly composed of four structural modules, namely (1) a wave-transparent skin; (2) preparing an aramid fiber honeycomb sandwich; (3) a reflecting plate; and (4) a bulletproof back plate. Wherein the wave-transparent skin is arranged on the outermost surface and receives incident electromagnetic waves, the aramid honeycomb sandwich, the reflecting plate and the bulletproof back plate are sequentially overlaid downwards, and all structural modules are bonded through modified resin adhesives. The ultra-wideband electromagnetic shielding and bulletproof composite structure material has a very excellent electromagnetic shielding effect, electromagnetic stealth of a target facility is achieved, meanwhile, certain protection performance is achieved, space occupation is reduced due to the multi-functionalization characteristic of the overall composite structure, and therefore the possibility that a target is detected is further reduced from the appearance; and the preparation raw materials of each structure module are rich, the cost is low, the operation process is simple, and industrial popularization and application of the ultra-wideband electromagnetic shielding and bulletproof composite structure material are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of electromagnetic absorbing materials, and specifically relates to an ultra-wideband electromagnetic shielding and bulletproof composite structural material and a preparation method thereof. Background Art

[0002] In today's world, with the rapid development of science and technology, modern military detection and guidance technology is not far behind. Due to the interference of electromagnetic waves, the global environment is "transparent" outside the line of sight, and the situation of electromagnetic radiation is becoming increasingly complicated. Especially in the military confrontation and national defense strategy of the country, electromagnetic detection has brought great threats to military targets on the battlefield. In order to meet the needs of the development of military technology and the construction of the national defense system, in special fields with major military needs such as fighters, submarines, ships, and shelters, the development of stealth technology is particularly important, and the development of electromagnetic shielding materials is indispensable.

[0003] The research and application technology of electromagnetic shielding materials has been developed since the Second World War. However, with the changes in the battlefield environment, the electromagnetic detection band of military equipment has been continuously expanded, and the traditional electromagnetic shielding materials have poor absorption effect or no absorption at all on higher frequency bands, resulting in important targets that take traditional stealth measures being completely exposed to the enemy's field of vision. Electromagnetic shielding materials can be divided into various categories according to the application form, such as coating type, patch type and structural type. Among them, honeycomb electromagnetic shielding materials, as a typical structural electromagnetic shielding material, have many advantages such as low density, high design freedom, good mechanical properties, corrosion resistance, temperature stability and good dielectric properties, and have been widely used in both military and civilian fields. The complex and changeable battlefield environment constantly requires traditional electromagnetic shielding materials to have multifunctional characteristics, thereby achieving the effect of hiding one's own military facilities and targets and confusing the enemy. Chinese patent CN113766820A discloses a carbon fiber tube reinforced external self-similar fractal composite electromagnetic shielding honeycomb structure plate, which is composed of two upper and lower panels and a honeycomb inner core, and has a balanced load-bearing performance and lightweight characteristics, and can meet the use requirements of spacecraft plates; Chinese patent CN113386449A discloses a manufacturing process for improving the structural strength of absorbing honeycomb sandwich panels, by slitting the honeycomb sandwich panel blank and machining the shape along the place filled with potting glue, without the need for subsequent edge sealing with adhesive film or prepreg, thereby enhancing the strength of the honeycomb sandwich panel after machining, making it not easy to break, and improving the surface quality; Chinese patent CN113394573A discloses a lightweight broadband absorbing material for high-power microwave darkrooms, which forms a three-dimensional periodic structure through high-temperature resistant absorbing sheets, in order to replace traditional absorbing materials such as sponges to reduce costs, and at the same time avoid fires caused by local high temperatures generated by concentrated microwave energy. It can be found that the existing processes are mostly aimed at enhancing the mechanical or thermal properties of honeycomb structures, and have achieved certain results, but at the same time there are also shortcomings such as limited improvement in quality and multifunctionality; moreover, the preparation process is complex, the production process is cumbersome, the improvement in broadband absorption effect is limited, and the cost reduction effect is not significant; especially in today's military equipment or facilities that need to achieve electromagnetic shielding while meeting certain protection performance, the existing honeycomb structure materials cannot meet them.

[0004] Therefore, in view of the above defects and shortcomings, the present invention provides an ultra-wideband electromagnetic shielding and bulletproof composite structural material and a preparation method thereof. Summary of the invention

[0005] The purpose of the present invention is to solve the problems that the current electromagnetic shielding material has a narrow absorption band, the composite structure material has a high preparation cost, a complex process, and does not have protective performance.

[0006] The present invention is realized through the following technical solutions:

[0007] An ultra-wideband electromagnetic shielding and bulletproof composite structural material, including a wave-transmitting skin; an aramid honeycomb sandwich; a reflector and a bulletproof back plate. The wave-transmitting skin is on the outermost surface, receiving incident electromagnetic waves, and the aramid honeycomb sandwich, the reflector and the bulletproof back plate are stacked downward in sequence, and the structural modules are bonded together using a modified resin adhesive.

[0008] An ultra-wideband electromagnetic shielding and bulletproof composite structural material and a preparation method thereof, the specific steps are as follows:

[0009] (1) Preparation of wave-transmitting skin

[0010] Step A1, weighing short glass fibers, nano-graphene powder and polymethyl methacrylate in a mass ratio of 20-30:5-7:40-50 respectively; and measuring tetrahydrofuran solvent in a mass volume ratio of 1 g:30-50 ml of short glass fibers and tetrahydrofuran solvent;

[0011] The particle size of the nano-graphene powder is 30 to 50 nm;

[0012] Step A2, dissolving the polymethyl methacrylate weighed in step A1 into tetrahydrofuran solvent, and using mechanical stirring, the stirring speed is 100-200 r / min, and a mixed solution A is obtained after 10-20 minutes; then the chopped glass fiber and nano-graphene powder weighed in step A1 are added to the mixed solution A, and mechanical stirring is maintained at a stirring speed of 300-500 r / min, and ultrasonic dispersion is performed at the same time, the ultrasonic power is 200 W, the frequency is 50 kHz, and a wave-transmitting skin resin dispersion is obtained after 30-50 minutes; then the wave-transmitting skin resin dispersion is placed in a 60-70° C. oven and allowed to stand for 1-3 hours to obtain a wave-transmitting skin resin prepreg;

[0013] Step A3, placing the wave-transmitting skin resin prepreg obtained in step A2 in a 300mmx300mm mold for paving, and controlling the thickness to be 0.3-0.5mm; then placing the paved mold in a 70-90°C oven for drying and curing, and obtaining a wave-transmitting skin precursor after 1 hour; then hot-pressing the wave-transmitting skin precursor at a temperature of 100°C and a holding time of 50s, and repeatedly hot-pressing for 3 times to obtain the wave-transmitting skin.

[0014] (2) Preparation of aramid honeycomb core

[0015] Step B1, respectively weighing epoxy resin, silicon carbide ceramic powder and nano iron oxide powder according to the mass ratio of epoxy resin, silicon carbide ceramic powder and nano iron oxide powder of 7-10:3-4:2-3; and measuring tetrahydrofuran solvent according to the mass volume ratio of epoxy resin to tetrahydrofuran solvent of 1g:20-30ml;

[0016] The particle size of the silicon carbide ceramic powder is 10 to 50 μm;

[0017] The particle size of the nano iron oxide powder is 20 to 30 nm;

[0018] Step B2, dissolving the epoxy resin weighed in step B1 in tetrahydrofuran solvent, and heating to 50-60°C, while mechanically stirring at a stirring speed of 100-200 r / min, and obtaining a mixed solution B after 5-10 minutes; then adding the silicon carbide ceramic powder and nano iron oxide powder weighed in step B1 to the mixed solution B, maintaining mechanical stirring at a stirring speed of 200-300 r / min, and dispersing by ultrasound at a power of 200 W and a frequency of 50 kHz, and obtaining a wave-absorbing resin dispersion after 20-30 minutes;

[0019] Step B3, placing the absorbing resin dispersion obtained in step B2 in a dipping tank, and then placing the aramid honeycomb core in the dipping tank for repeated dipping and drying at room temperature until the thickness W2 of the absorbing layer reaches 0.3-0.5 mm; then placing the impregnated aramid honeycomb core in a 100-120° C. oven, and drying for 2-3 hours to obtain an aramid honeycomb sandwich core;

[0020] The specification of the aramid honeycomb core is 300mmx300mm, a single cell is a regular hexagon, a side length W is 5mm, a thickness W1 is 0.2-0.3mm, and a height h is 10-15mm.

[0021] (3) Preparation of reflector

[0022] Step C1, respectively weighing graphene and polymethyl methacrylate according to a mass ratio of graphene to polymethyl methacrylate of 1 to 2:20; and measuring tetrahydrofuran solvent according to a mass volume ratio of polymethyl methacrylate to tetrahydrofuran solvent of 1g:20 to 30ml; then dissolving graphene and polymethyl methacrylate in tetrahydrofuran solvent, using mechanical stirring, the stirring speed is 100 to 200r / min, and ultrasonic dispersion is performed at the same time, the ultrasonic power is 200W, the frequency is 50kHz, and a reflective resin dispersion is obtained after 30 to 40 minutes; then placing the reflective resin dispersion in a 70 to 80°C oven, and obtaining a reflective resin glue solution after 1 hour;

[0023] In step C2, the reflective resin glue in step C1 is repeatedly applied on the surface of the carbon fiber cloth and dried until the thickness reaches 0.5-0.7 mm, thereby obtaining a reflective plate precursor; the reflective plate precursor is then hot-pressed at a temperature of 160° C. for a holding time of 30 seconds, and the hot-pressing is repeated 4 times to obtain a reflective plate;

[0024] The carbon fiber cloth is a carbon fiber flat cloth or a woven cloth, and the specification is 300mmx300mm.

[0025] (4) Preparation of modified resin adhesive

[0026] Weigh urea-formaldehyde resin, terpene resin, nano nickel powder, 1,4-butanediol, and titanate coupling agent CS-101 at a mass ratio of 25-30:15-20:5-10:3-5:1-3 respectively; and measure tetrahydrofuran solvent at a mass volume ratio of urea-formaldehyde resin to tetrahydrofuran solvent of 1g:20-30ml, and add urea-formaldehyde resin, terpene resin, and titanate coupling agent CS-101 into tetrahydrofuran solvent for mechanical stirring at a speed of 300-500r / m in, and a pretreated resin dispersion is obtained after 20 to 30 minutes; then, nano nickel powder and 1,4-butanediol are added to the pretreated resin dispersion, and mechanical stirring is continued at a speed of 500 to 700 r / min, and ultrasonic dispersion is performed at the same time, with an ultrasonic power of 500 W and a frequency of 50 kHz, and a modified resin mixed liquid is obtained after 60 to 100 minutes; the modified resin mixed liquid is placed in an oven at 60 to 80° C. for 2 to 3 hours to obtain a modified resin adhesive.

[0027] (5) Preparation of bulletproof backboard

[0028] Step D1, stacking and compounding 20 to 30 layers of aramid non-woven fabrics, applying a layer of modified resin adhesive between each layer, and standing at room temperature for 3 to 5 hours to obtain an aramid board;

[0029] Step D2, hot pressing the aramid plate obtained in step D1 at a temperature of 120° C. for a holding time of 20 seconds, and repeating this process 3 times to obtain a bulletproof back plate;

[0030] The specification of the aramid non-woven fabric is 300mmx300mm;

[0031] (6) Composite structure modules

[0032] Step E1, using a modified resin adhesive (5) to sequentially adhere the wave-transmitting skin (1), the aramid honeycomb core (2), the reflector (3), and the bulletproof backboard (4) in a top-down order, wherein the thickness of the modified resin adhesive layer is controlled to be 0.2 to 0.3 mm, thereby obtaining a prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material;

[0033] Step E2: placing the prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material in step E1 in an oven at 120-140° C., and drying for 2-3 hours to obtain the ultra-wideband electromagnetic shielding and bulletproof composite structural material.

[0034] Beneficial Effects

[0035] 1. An ultra-wideband electromagnetic shielding and bulletproof composite structural material and its preparation method, which significantly improves the electromagnetic shielding efficiency through the functional design of structural gradient and combines the resistance loss, dielectric loss and magnetic loss, so that it has a very excellent electromagnetic shielding effect in the ultra-wideband range of 1 to 45 GHz;

[0036] 2. An ultra-wideband electromagnetic shielding and bulletproof composite structural material and its preparation method, which has protective performance by adding a bulletproof plate on the back, achieving electromagnetic invisibility of target facilities while having certain protective performance; and the aramid honeycomb core is coated with an epoxy resin-based absorbing layer, which dissipates electromagnetic energy while providing sufficient mechanical support for the aramid sandwich structure layer. The multifunctional characteristics of the overall composite structure reduce space occupancy, thereby further reducing the possibility of target detection from the appearance;

[0037] 3. An ultra-wideband electromagnetic shielding and bulletproof composite structural material and its preparation method. The raw materials for the preparation of each structural module are abundant and low-cost. At the same time, by using modified resin adhesives, there is no odor, fast curing speed, simple operation process, and no three wastes are generated during the preparation process, which meets the requirements of green and environmentally friendly sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic diagram of the structural layering of the ultra-wideband electromagnetic shielding and bulletproof composite structural material of the present invention;

[0039] Figure 2 It is a schematic diagram of the structure of a single aramid honeycomb of the present invention;

[0040] Figure 3 A top view of the ultra-wideband electromagnetic shielding and bulletproof composite structural material.

[0041] Figure numerals: 1. wave-transmitting skin; 2. aramid honeycomb core; 3. reflector; 4. bulletproof back plate; 5. modified resin adhesive; 6. aramid honeycomb paper; 7. composite wave-absorbing resin.

[0042] Where W is the cell side length of a single aramid honeycomb; W1 is the thickness of the aramid honeycomb paper; and W2 is the thickness of the absorbing layer. DETAILED DESCRIPTION

[0043] The following embodiments are further explanations of the present invention, which are partial embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without any creative work belong to the scope of protection of the present invention.

[0044] Example 1

[0045] (1) Preparation of wave-transmitting skin 1

[0046] 83g of polymethyl methacrylate was dissolved in 1600ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 120r / min, and a mixed solution A was obtained after 15min; then 50g of chopped glass fiber and 12g of nano-graphene powder were added to the mixed solution A, and mechanical stirring was maintained at a stirring speed of 380r / min, and ultrasonic dispersion was performed at the same time, with an ultrasonic power of 200W and a frequency of 50kHz, and a wave-transmitting skin resin dispersion was obtained after 40min; then the wave-transmitting skin resin dispersion was placed in a 64°C oven and allowed to stand for 1.8h to obtain a wave-transmitting skin resin prepreg;

[0047] The above-mentioned wave-transmitting skin resin prepreg is placed in a 300mmx300mm mold and laid with a thickness of 0.4mm; the laid mold is then placed in a 75°C oven for drying and curing, and a wave-transmitting skin precursor is obtained after 1 hour; the wave-transmitting skin precursor is then hot-pressed at a temperature of 100°C and a holding time of 50s, and the wave-transmitting skin 1 is obtained by repeating the hot pressing 3 times.

[0048] (2) Preparation of aramid honeycomb core 2

[0049] 60g of epoxy resin was dissolved in 1500ml of tetrahydrofuran solvent, and the temperature was raised to 54°C, and mechanical stirring was performed at a stirring speed of 180r / min. After 7min, a mixed solution B was obtained; then 27g of silicon carbide ceramic powder and 16g of nano iron oxide powder were added to the mixed solution B, and mechanical stirring was maintained at a stirring speed of 260r / min. Ultrasonic dispersion was performed at a power of 200W and a frequency of 50kHz. After 22min, a microwave absorbing resin dispersion was obtained;

[0050] The above-mentioned absorbing resin dispersion is placed in a dipping tank, and then the aramid honeycomb core is placed in the dipping tank for repeated dipping and drying at room temperature until the thickness W2 of the absorbing layer reaches 0.5 mm; then the impregnated aramid honeycomb core is placed in a 110° C. oven and dried for 2.4 hours to obtain the aramid honeycomb sandwich core 2;

[0051] (3) Preparation of reflector 3

[0052] 3.5 g of graphene and 50 g of polymethyl methacrylate were dissolved in 1200 ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 130 r / min. Ultrasonic dispersion was performed at a power of 200 W and a frequency of 50 kHz. After 34 minutes, a reflective resin dispersion was obtained. The reflective resin dispersion was then placed in a 78° C. oven, and after 1 hour, a reflective resin glue solution was obtained.

[0053] The reflective resin glue is repeatedly applied on the surface of the carbon fiber cloth and dried until the thickness reaches 0.6 mm, thereby obtaining a reflective plate precursor; the reflective plate precursor is then hot-pressed at a temperature of 160° C. for a holding time of 30 seconds, and the hot-pressing is repeated 4 times to obtain a reflective plate 3;

[0054] (4) Preparation of modified resin adhesive 5

[0055] 100g urea-formaldehyde resin, 65g terpene resin and 7g titanate coupling agent CS-101 were added to 2200ml tetrahydrofuran solvent and mechanically stirred at a speed of 400r / min. After 25min, a pretreated resin dispersion was obtained; then 32g nano nickel powder and 16g 1,4-butanediol were added to the pretreated resin dispersion, and mechanical stirring was continued at a speed of 580r / min. Ultrasonic dispersion was performed at a power of 500W and a frequency of 50kHz. After 75min, a modified resin mixture was obtained; the modified resin mixture was placed in an oven at 75°C for 2.2h to obtain a modified resin adhesive 5.

[0056] (5) Preparation of bulletproof back plate 4

[0057] 24 layers of aramid non-woven fabrics are laminated, a layer of modified resin adhesive is applied between each layer, and the aramid plate is left standing at room temperature for 3.5 hours to obtain an aramid plate; the aramid plate is hot-pressed at a temperature of 120° C. for a holding time of 20 seconds, and the process is repeated 3 times to obtain a bulletproof back plate 4;

[0058] (6) Composite structure modules

[0059] The above structural modules are bonded in the order of wave-transmitting skin 1, aramid honeycomb core 2, reflector 3, and bulletproof back plate 4 from top to bottom using modified resin adhesive 5, and the thickness of the modified resin adhesive layer is 0.2 mm, so as to obtain a prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material;

[0060] The prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material is placed in an oven at 130° C. and dried for 2.5 hours to obtain the ultra-wideband electromagnetic shielding and bulletproof composite structural material.

[0061] Note: The average particle size of the nano-graphene powder used in this embodiment is 30-40 nm; the average particle size of the silicon carbide ceramic powder is 10-20 μm; the average particle size of the nano-iron oxide powder is 20-25 nm; the aramid honeycomb core has a specification of 300 mm x 300 mm, a single cell is a regular hexagon, a side length W of 5 mm, a thickness W1 of 0.2 mm, and a height h of 12 mm; the carbon fiber cloth is a carbon fiber non-woven cloth.

[0062] Example 2

[0063] (1) Preparation of wave-transmitting skin 1

[0064] 140g of polymethyl methacrylate was dissolved in 2300ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 160r / min, and a mixed solution A was obtained after 14 minutes; then 70g of chopped glass fiber and 18g of nano-graphene powder were added to the mixed solution A, and mechanical stirring was maintained at a stirring speed of 460r / min, and ultrasonic dispersion was performed at the same time, with an ultrasonic power of 200W and a frequency of 50kHz, and a wave-transmitting skin resin dispersion was obtained after 35 minutes; then the wave-transmitting skin resin dispersion was placed in a 62°C oven and allowed to stand for 2.2h to obtain a wave-transmitting skin resin prepreg;

[0065] The above-mentioned wave-transmitting skin resin prepreg is placed in a 300mmx300mm mold and laid with a thickness of 0.3mm; the laid mold is then placed in a 74°C oven for drying and curing, and a wave-transmitting skin precursor is obtained after 1 hour; the wave-transmitting skin precursor is then hot-pressed at a temperature of 100°C and a holding time of 50s, and the wave-transmitting skin 1 is obtained by repeating the hot pressing 3 times.

[0066] (2) Preparation of aramid honeycomb core 2

[0067] 75g of epoxy resin was dissolved in 1700ml of tetrahydrofuran solvent, and the temperature was raised to 58°C, and mechanical stirring was performed at a stirring speed of 110r / min. After 9 minutes, a mixed solution B was obtained; then 30g of silicon carbide ceramic powder and 21g of nano iron oxide powder were added to the mixed solution B, and mechanical stirring was maintained at a stirring speed of 250r / min. Ultrasonic dispersion was performed at a power of 200W and a frequency of 50kHz. After 25 minutes, a microwave-absorbing resin dispersion was obtained;

[0068] The above-mentioned absorbing resin dispersion is placed in a dipping tank, and then the aramid honeycomb core is placed in the dipping tank for repeated dipping and drying at room temperature until the thickness W2 of the absorbing layer reaches 0.3 mm; then the impregnated aramid honeycomb core is placed in a 120° C. oven and dried for 2.6 hours to obtain the aramid honeycomb sandwich core 2;

[0069] (3) Preparation of reflector 3

[0070] 5.6 g of graphene and 70 g of polymethyl methacrylate were dissolved in 1600 ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 170 r / min. Ultrasonic dispersion was performed at a power of 200 W and a frequency of 50 kHz. After 36 minutes, a reflective resin dispersion was obtained. The reflective resin dispersion was then placed in a 72° C. oven, and after 1 hour, a reflective resin glue solution was obtained.

[0071] The reflective resin glue is repeatedly applied on the surface of the carbon fiber cloth and dried until the thickness reaches 0.5 mm, thereby obtaining a reflective plate precursor; the reflective plate precursor is then hot-pressed at a temperature of 160° C. for a holding time of 30 seconds, and the hot-pressing is repeated 4 times to obtain a reflective plate 3;

[0072] (4) Preparation of modified resin adhesive 5

[0073] 130g urea-formaldehyde resin, 90g terpene resin and 9g titanate coupling agent CS-101 were added to 3000ml tetrahydrofuran solvent and mechanically stirred at a speed of 450r / min. After 22min, a pretreated resin dispersion was obtained; then 42g nano nickel powder and 18g 1,4-butanediol were added to the pretreated resin dispersion, and mechanical stirring was continued at a speed of 620r / min. Ultrasonic dispersion was performed at the same time, with an ultrasonic power of 500W and a frequency of 50kHz. After 90min, a modified resin mixture was obtained; the modified resin mixture was placed in a 70°C oven for 2.5h to obtain a modified resin adhesive 5.

[0074] (5) Preparation of bulletproof back plate 4

[0075] 28 layers of aramid non-woven fabrics are laminated, a layer of modified resin adhesive is applied between each layer, and the aramid plate is left standing at room temperature for 4.5 hours to obtain an aramid plate; the aramid plate is hot-pressed at a temperature of 120° C. for a holding time of 20 seconds, and the process is repeated 3 times to obtain a bulletproof back plate 4;

[0076] (6) Composite structure modules

[0077] The above structural modules are bonded in the order of wave-transmitting skin 1, aramid honeycomb core 2, reflector 3, and bulletproof back plate 4 from top to bottom using modified resin adhesive 5, and the thickness of the modified resin adhesive layer is 0.3 mm, so as to obtain a prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material;

[0078] The prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material is placed in an oven at 125° C. and dried for 2.6 hours to obtain the ultra-wideband electromagnetic shielding and bulletproof composite structural material.

[0079] Note: The average particle size of the nano-graphene powder used in this embodiment is 40-50 nm; the average particle size of the silicon carbide ceramic powder is 30-40 μm; the average particle size of the nano-iron oxide powder is 25-30 nm; the aramid honeycomb core has a specification of 300 mm x 300 mm, a single cell is a regular hexagon, a side length W of 5 mm, a thickness W1 of 0.3 mm, and a height h of 15 mm; the carbon fiber cloth is a carbon fiber woven cloth.

[0080] Example 3

[0081] (1) Preparation of wave-transmitting skin 1

[0082] 180g of polymethyl methacrylate was dissolved in 4000ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 150r / min, and a mixed solution A was obtained after 17min; then 110g of chopped glass fiber and 26g of nano-graphene powder were added to the mixed solution A, and mechanical stirring was maintained at a stirring speed of 420r / min, and ultrasonic dispersion was performed at an ultrasonic power of 200W and a frequency of 50kHz, and a wave-transmitting skin resin dispersion was obtained after 45min; then the wave-transmitting skin resin dispersion was placed in a 68°C oven and allowed to stand for 2.6h to obtain a wave-transmitting skin resin prepreg;

[0083] The above-mentioned wave-transmitting skin resin prepreg is placed in a 300mmx300mm mold and laid with a thickness of 0.5mm; the laid mold is then placed in a 72°C oven for drying and curing, and a wave-transmitting skin precursor is obtained after 1 hour; the wave-transmitting skin precursor is then hot-pressed at a temperature of 100°C and a holding time of 50s, and the wave-transmitting skin 1 is obtained by repeating the hot pressing 3 times.

[0084] (2) Preparation of aramid honeycomb core 2

[0085] 80g of epoxy resin was dissolved in 2000ml of tetrahydrofuran solvent, and the temperature was raised to 56°C, and mechanical stirring was performed at a stirring speed of 190r / min. After 8min, a mixed solution B was obtained; then 32g of silicon carbide ceramic powder and 24g of nano iron oxide powder were added to the mixed solution B, and mechanical stirring was maintained at a stirring speed of 240r / min. Ultrasonic dispersion was performed at a power of 200W and a frequency of 50kHz. After 27min, a microwave-absorbing resin dispersion was obtained;

[0086] The above-mentioned absorbing resin dispersion is placed in a dipping tank, and then the aramid honeycomb core is placed in the dipping tank for repeated dipping and drying at room temperature until the thickness W2 of the absorbing layer reaches 0.4 mm; then the impregnated aramid honeycomb core is placed in a 115° C. oven and dried for 2.5 hours to obtain the aramid honeycomb sandwich core 2;

[0087] (3) Preparation of reflector 3

[0088] 4.8 g of graphene and 60 g of polymethyl methacrylate were dissolved in 1500 ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 140 r / min. Ultrasonic dispersion was performed at an ultrasonic power of 200 W and a frequency of 50 kHz. After 38 minutes, a reflective resin dispersion was obtained. The reflective resin dispersion was then placed in a 75° C. oven, and after 1 hour, a reflective resin glue solution was obtained.

[0089] The reflective resin glue is repeatedly applied on the surface of the carbon fiber cloth and dried until the thickness reaches 0.7 mm, thereby obtaining a reflective plate precursor; the reflective plate precursor is then hot-pressed at a temperature of 160° C. for a holding time of 30 seconds, and the hot-pressing is repeated 4 times to obtain a reflective plate 3;

[0090] (4) Preparation of modified resin adhesive 5

[0091] 160g urea-formaldehyde resin, 110g terpene resin and 13g titanate coupling agent CS-101 were added to 4500ml tetrahydrofuran solvent and mechanically stirred at a speed of 350r / min. After 30min, a pretreated resin dispersion was obtained; then 55g nano nickel powder and 26g 1,4-butanediol were added to the pretreated resin dispersion, and mechanical stirring was continued at a speed of 660r / min. Ultrasonic dispersion was performed at a power of 500W and a frequency of 50kHz. After 85min, a modified resin mixture was obtained; the modified resin mixture was placed in an oven at 65°C for 2.8h to obtain a modified resin adhesive 5.

[0092] (5) Preparation of bulletproof back plate 4

[0093] 26 layers of aramid non-woven fabrics are laminated, a layer of modified resin adhesive is applied between each layer, and the aramid plate is left standing at room temperature for 4 hours to obtain the aramid plate; the aramid plate is hot-pressed at a temperature of 120° C. for a holding time of 20 seconds, and the process is repeated 3 times to obtain the bulletproof back plate 4;

[0094] (6) Composite structure modules

[0095] The above structural modules are bonded in the order of wave-transmitting skin 1, aramid honeycomb core 2, reflector 3, and bulletproof back plate 4 from top to bottom using modified resin adhesive 5, and the thickness of the modified resin adhesive layer is 0.25 mm, so as to obtain a prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material;

[0096] The prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material is placed in an oven at 135° C. and dried for 2.4 hours to obtain the ultra-wideband electromagnetic shielding and bulletproof composite structural material.

[0097] Note: The average particle size of the nano-graphene powder used in this embodiment is 35-45 nm; the average particle size of the silicon carbide ceramic powder is 20-30 μm; the average particle size of the nano-iron oxide powder is 22-26 nm; the aramid honeycomb core has a specification of 300 mm x 300 mm, a single cell is a regular hexagon, a side length W of 5 mm, a thickness W1 of 0.25 mm, and a height h of 14 mm; the carbon fiber cloth is a carbon fiber non-woven cloth.

[0098] Example 4

[0099] (1) Preparation of wave-transmitting skin 1

[0100] 180g of polymethyl methacrylate was dissolved in 4000ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 100r / min, and a mixed solution A was obtained after 10min; then 110g of chopped glass fiber and 26g of nano-graphene powder were added to the mixed solution A, and mechanical stirring was maintained at a stirring speed of 300r / min, and ultrasonic dispersion was performed at an ultrasonic power of 200W and a frequency of 50kHz, and a wave-transmitting skin resin dispersion was obtained after 30min; then the wave-transmitting skin resin dispersion was placed in a 60°C oven and allowed to stand for 1h to obtain a wave-transmitting skin resin prepreg;

[0101] The above-mentioned wave-transmitting skin resin prepreg is placed in a 300mmx300mm mold and laid with a thickness of 0.3mm; the laid mold is then placed in a 70°C oven for drying and curing, and a wave-transmitting skin precursor is obtained after 1 hour; the wave-transmitting skin precursor is then hot-pressed at a temperature of 100°C and a holding time of 50s, and the wave-transmitting skin 1 is obtained by repeating the hot pressing 3 times.

[0102] (2) Preparation of aramid honeycomb core 2

[0103] 80g of epoxy resin was dissolved in 2000ml of tetrahydrofuran solvent, and the temperature was raised to 50°C, and mechanical stirring was performed at a stirring speed of 100r / min. After 5min, a mixed solution B was obtained; then 32g of silicon carbide ceramic powder and 24g of nano iron oxide powder were added to the mixed solution B, and mechanical stirring was maintained at a stirring speed of 200r / min. Ultrasonic dispersion was performed at a power of 200W and a frequency of 50kHz. After 20min, a wave-absorbing resin dispersion was obtained;

[0104] The above-mentioned absorbing resin dispersion is placed in a dipping tank, and then the aramid honeycomb core is placed in the dipping tank for repeated dipping and drying at room temperature until the thickness W2 of the absorbing layer reaches 0.4 mm; then the impregnated aramid honeycomb core is placed in a 115° C. oven and dried for 2.5 hours to obtain the aramid honeycomb sandwich core 2;

[0105] (3) Preparation of reflector 3

[0106] 4.8 g of graphene and 60 g of polymethyl methacrylate were dissolved in 1500 ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 100 r / min. Ultrasonic dispersion was performed at a power of 200 W and a frequency of 50 kHz. After 30 minutes, a reflective resin dispersion was obtained. The reflective resin dispersion was then placed in a 70° C. oven, and after 1 hour, a reflective resin glue solution was obtained.

[0107] The reflective resin glue is repeatedly applied on the surface of the carbon fiber cloth and dried until the thickness reaches 0.7 mm, thereby obtaining a reflective plate precursor; the reflective plate precursor is then hot-pressed at a temperature of 160° C. for a holding time of 30 seconds, and the hot-pressing is repeated 4 times to obtain a reflective plate 3;

[0108] (4) Preparation of modified resin adhesive 5

[0109] 160g of urea-formaldehyde resin, 110g of terpene resin, and 13g of titanate coupling agent CS-101 were added to 4500ml of tetrahydrofuran solvent and mechanically stirred at a speed of 300r / min. After 20min, a pretreated resin dispersion was obtained; then 55g of nano nickel powder and 26g of 1,4-butanediol were added to the pretreated resin dispersion, and mechanical stirring was continued at a speed of 500r / min. Ultrasonic dispersion was performed at the same time, with an ultrasonic power of 500W and a frequency of 50kHz. After 60min, a modified resin mixture was obtained; the modified resin mixture was placed in an oven at 60°C for 2h to obtain a modified resin adhesive 5.

[0110] (5) Preparation of bulletproof back plate 4

[0111] 20 layers of aramid non-woven fabrics are laminated, a layer of modified resin adhesive is applied between each layer, and the aramid plate is allowed to stand at room temperature for 3 hours to obtain an aramid plate; the aramid plate is hot-pressed at a temperature of 120° C. for a holding time of 20 seconds, and the process is repeated 3 times to obtain a bulletproof back plate 4;

[0112] (6) Composite structure modules

[0113] The above structural modules are bonded in order from top to bottom, namely, the wave-transmitting skin 1, the aramid honeycomb sandwich 2, the reflector 3, and the bulletproof back plate 4, using a modified resin adhesive 5, wherein the thickness of the modified resin adhesive layer is 0.2 mm, thereby obtaining a prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material;

[0114] The prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material is placed in an oven at 120° C. and dried for 2 hours to obtain the ultra-wideband electromagnetic shielding and bulletproof composite structural material.

[0115] Note: The average particle size of the nano-graphene powder used in this embodiment is 35-45 nm; the average particle size of the silicon carbide ceramic powder is 20-30 μm; the average particle size of the nano-iron oxide powder is 22-26 nm; the aramid honeycomb core has a specification of 300 mm x 300 mm, a single cell is a regular hexagon, a side length W of 5 mm, a thickness W1 of 0.25 mm, and a height h of 14 mm; the carbon fiber cloth is a carbon fiber non-woven cloth.

[0116] Example 5

[0117] (1) Preparation of wave-transmitting skin 1

[0118] 180g of polymethyl methacrylate was dissolved in 4000ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 200r / min, and a mixed solution A was obtained after 20min; then 110g of chopped glass fiber and 26g of nano-graphene powder were added to the mixed solution A, and mechanical stirring was maintained at a stirring speed of 500r / min, and ultrasonic dispersion was performed at the same time, with an ultrasonic power of 200W and a frequency of 50kHz, and a wave-transmitting skin resin dispersion was obtained after 50min; then the wave-transmitting skin resin dispersion was placed in a 70°C oven and allowed to stand for 3h to obtain a wave-transmitting skin resin prepreg;

[0119] The above-mentioned wave-transmitting skin resin prepreg is placed in a 300mmx300mm mold and laid with a thickness of 0.5mm; the laid mold is then placed in a 90°C oven for drying and curing, and a wave-transmitting skin precursor is obtained after 1 hour; the wave-transmitting skin precursor is then hot-pressed at a temperature of 100°C and a holding time of 50s, and the wave-transmitting skin 1 is obtained by repeating the hot pressing 3 times.

[0120] (2) Preparation of aramid honeycomb core 2

[0121] 80g of epoxy resin was dissolved in 2000ml of tetrahydrofuran solvent, and the temperature was raised to 60°C, and mechanical stirring was performed at a stirring speed of 200r / min. After 10min, a mixed solution B was obtained; then 32g of silicon carbide ceramic powder and 24g of nano iron oxide powder were added to the mixed solution B, and mechanical stirring was maintained at a stirring speed of 300r / min. Ultrasonic dispersion was performed at a power of 200W and a frequency of 50kHz. After 30min, a wave-absorbing resin dispersion was obtained;

[0122] The above-mentioned absorbing resin dispersion is placed in a dipping tank, and then the aramid honeycomb core is placed in the dipping tank for repeated dipping and drying at room temperature until the thickness W2 of the absorbing layer reaches 0.5 mm; then the impregnated aramid honeycomb core is placed in a 120° C. oven and dried for 3 hours to obtain the aramid honeycomb sandwich core 2;

[0123] (3) Preparation of reflector 3

[0124] 4.8g of graphene and 60g of polymethyl methacrylate were dissolved in 1500ml of tetrahydrofuran solvent, and mechanical stirring was used at a stirring speed of 200r / min. Ultrasonic dispersion was performed at a power of 200W and a frequency of 50kHz. After 40min, a reflective resin dispersion was obtained. The reflective resin dispersion was then placed in an oven at 80°C, and after 1h, a reflective resin glue solution was obtained.

[0125] The reflective resin glue is repeatedly applied on the surface of the carbon fiber cloth and dried until the thickness reaches 0.7 mm, thereby obtaining a reflective plate precursor; the reflective plate precursor is then hot-pressed at a temperature of 160° C. for a holding time of 30 seconds, and the hot-pressing is repeated 4 times to obtain a reflective plate 3;

[0126] (4) Preparation of modified resin adhesive 5

[0127] 160g of urea-formaldehyde resin, 110g of terpene resin, and 13g of titanate coupling agent CS-101 were added to 4500ml of tetrahydrofuran solvent and mechanically stirred at a speed of 500r / min. After 30min, a pretreated resin dispersion was obtained; then 55g of nano nickel powder and 26g of 1,4-butanediol were added to the pretreated resin dispersion, and mechanical stirring was continued at a speed of 500r / min. Ultrasonic dispersion was performed at the same time, with an ultrasonic power of 500W and a frequency of 50kHz. After 100min, a modified resin mixture was obtained; the modified resin mixture was placed in an oven at 80°C for 3h to obtain a modified resin adhesive 5.

[0128] (5) Preparation of bulletproof back plate 4

[0129] 30 layers of aramid non-woven fabrics are laminated, a layer of modified resin adhesive is applied between each layer, and the aramid plate is allowed to stand at room temperature for 5 hours to obtain an aramid plate; the aramid plate is hot-pressed at a temperature of 120° C. for a holding time of 20 seconds, and the process is repeated 3 times to obtain a bulletproof back plate 4;

[0130] (6) Composite structure modules

[0131] The above structural modules are bonded in the order of wave-transmitting skin 1, aramid honeycomb core 2, reflector 3, and bulletproof back plate 4 from top to bottom using modified resin adhesive 5, and the thickness of the modified resin adhesive layer is 0.3 mm, so as to obtain a prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material;

[0132] The prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material is placed in an oven at 140° C. and dried for 3 hours to obtain the ultra-wideband electromagnetic shielding and bulletproof composite structural material.

[0133] Note: The average particle size of the nano-graphene powder used in this embodiment is 35-45 nm; the average particle size of the silicon carbide ceramic powder is 20-30 μm; the average particle size of the nano-iron oxide powder is 22-26 nm; the aramid honeycomb core has a specification of 300 mm x 300 mm, a single cell is a regular hexagon, a side length W of 5 mm, a thickness W1 of 0.25 mm, and a height h of 14 mm; the carbon fiber cloth is a carbon fiber non-woven cloth.

[0134] Effect verification

[0135] The ultra-wideband electromagnetic shielding and bulletproof composite structural materials prepared in Example 1, Example 2 and Example 3 were subjected to performance tests. The electromagnetic shielding performance test results showed that the electromagnetic shielding effect was excellent, the reflectivity of 1 to 18 GHz was better than -30 dB, the reflectivity of 18 to 26.5 GHz was better than -35 dB, and the reflectivity of 26.5 to 45 GHz was better than -25 dB; the ballistic performance test results showed that the ballistic performance was excellent, the concave value was less than 20 mm, and the bulletproof standard of the Ministry of Public Security was met.

Claims

1. An ultra-wideband electromagnetic shielding and bulletproof composite structural material, characterized in that: The ultra-wideband electromagnetic shielding and bulletproof composite structural material comprises a wave-transmitting skin (1), an aramid honeycomb sandwich core (2), a reflector (3) and a bulletproof back plate (4); wherein the wave-transmitting skin (1) is on the outermost surface, receiving incident electromagnetic waves, and the aramid honeycomb sandwich core (2), the reflector (3) and the bulletproof back plate (4) are sequentially stacked downward, and each structural module is bonded together using a modified resin adhesive (5).

2. The ultra-wideband electromagnetic shielding and bulletproof composite structural material according to claim 1, characterized in that: The preparation steps of the wave-transmitting skin (1) are as follows: Step A1, weighing short glass fibers, nano-graphene powder and polymethyl methacrylate in a mass ratio of 20-30:5-7:40-50 respectively; and measuring tetrahydrofuran solvent in a mass volume ratio of 1 g:30-50 ml of short glass fibers and tetrahydrofuran solvent; The particle size of the nano-graphene powder is 30 to 50 nm; Step A2, dissolving the polymethyl methacrylate weighed in step A1 into tetrahydrofuran solvent, and using mechanical stirring, the stirring speed is 100-200 r / min, and a mixed solution A is obtained after 10-20 minutes; then the chopped glass fiber and nano-graphene powder weighed in step A1 are added to the mixed solution A, and mechanical stirring is maintained at a stirring speed of 300-500 r / min, and ultrasonic dispersion is performed at the same time, the ultrasonic power is 200 W, the frequency is 50 kHz, and a wave-transmitting skin resin dispersion is obtained after 30-50 minutes; then the wave-transmitting skin resin dispersion is placed in a 60-70° C. oven and allowed to stand for 1-3 hours to obtain a wave-transmitting skin resin prepreg; Step A3, placing the wave-transmitting skin resin prepreg obtained in step A2 in a 300mmx300mm mold for paving, and controlling the thickness to be 0.3-0.5mm; then placing the paved mold in a 70-90°C oven for drying and curing, and obtaining a wave-transmitting skin precursor after 1 hour; then hot-pressing the wave-transmitting skin precursor at a temperature of 100°C and a holding time of 50s, and repeatedly hot-pressing for 3 times to obtain the wave-transmitting skin.

3. The ultra-wideband electromagnetic shielding and bulletproof composite structural material according to claim 1, characterized in that: The steps for preparing the aramid honeycomb sandwich (2) are as follows: Step B1, respectively weighing epoxy resin, silicon carbide ceramic powder and nano iron oxide powder according to the mass ratio of epoxy resin, silicon carbide ceramic powder and nano iron oxide powder of 7-10:3-4:2-3; and measuring tetrahydrofuran solvent according to the mass volume ratio of epoxy resin to tetrahydrofuran solvent of 1g:20-30ml; The particle size of the silicon carbide ceramic powder is 10 to 50 μm; The particle size of the nano iron oxide powder is 20 to 30 nm; Step B2, dissolving the epoxy resin weighed in step B1 in tetrahydrofuran solvent, and heating to 50-60°C, while mechanically stirring at a stirring speed of 100-200 r / min, and obtaining a mixed solution B after 5-10 minutes; then adding the silicon carbide ceramic powder and nano iron oxide powder weighed in step B1 to the mixed solution B, maintaining mechanical stirring at a stirring speed of 200-300 r / min, and dispersing by ultrasound at a power of 200 W and a frequency of 50 kHz, and obtaining a wave-absorbing resin dispersion after 20-30 minutes; Step B3, placing the absorbing resin dispersion obtained in step B2 in a dipping tank, then placing the aramid honeycomb core in the dipping tank for repeated dipping and drying at room temperature until the thickness W2 of the absorbing layer reaches 0.3-0.5 mm; then placing the impregnated aramid honeycomb core in a 100-120° C. oven, and drying for 2-3 hours to obtain the aramid honeycomb sandwich.

4. The ultra-wideband electromagnetic shielding and bulletproof composite structural material according to claim 1, characterized in that: The steps for preparing the reflector (3) are as follows: Step C1, respectively weighing graphene and polymethyl methacrylate according to a mass ratio of graphene to polymethyl methacrylate of 1 to 2:20; and measuring tetrahydrofuran solvent according to a mass volume ratio of polymethyl methacrylate to tetrahydrofuran solvent of 1g:20 to 30ml; then dissolving graphene and polymethyl methacrylate in tetrahydrofuran solvent, using mechanical stirring, the stirring speed is 100 to 200r / min, and ultrasonic dispersion is performed at the same time, the ultrasonic power is 200W, the frequency is 50kHz, and a reflective resin dispersion is obtained after 30 to 40 minutes; then placing the reflective resin dispersion in a 70 to 80°C oven, and obtaining a reflective resin glue solution after 1 hour; In step C2, the reflective resin glue in step C1 is repeatedly applied to the surface of the carbon fiber cloth and dried until the thickness reaches 0.5-0.7 mm, thereby obtaining a reflective plate precursor; the reflective plate precursor is then hot-pressed at a temperature of 160° C. for 30 seconds, and the hot-pressing is repeated 4 times to obtain a reflective plate.

5. The ultra-wideband electromagnetic shielding and bulletproof composite structural material according to claim 1, characterized in that: The preparation method of the modified resin adhesive (5) is as follows: urea-formaldehyde resin, terpene resin, nano nickel powder, 1,4-butanediol, and titanate coupling agent CS-101 are weighed in a mass ratio of 25-30:15-20:5-10:3-5:1-3 respectively; tetrahydrofuran solvent is measured in a mass volume ratio of 1g:20-30ml of urea-formaldehyde resin to tetrahydrofuran solvent, and urea-formaldehyde resin, terpene resin, and titanate coupling agent CS-101 are added to the tetrahydrofuran solvent for mechanical stirring at a rotation speed of 300~500r / min, after 20~30min, a pretreated resin dispersion is obtained; then, nano nickel powder and 1,4-butanediol are added to the pretreated resin dispersion, and mechanical stirring is continued at a speed of 500~700r / min, and ultrasonic dispersion is performed at the same time, with an ultrasonic power of 500W and a frequency of 50kHz, and after 60~100min, a modified resin mixture is obtained; the modified resin mixture is placed in an oven at 60~80℃ for 2~3h to obtain a modified resin adhesive.

6. The ultra-wideband electromagnetic shielding and bulletproof composite structural material according to claim 5, characterized in that: The preparation steps of the bulletproof back plate (4) are: Step D1, stacking and compounding 20 to 30 layers of aramid non-woven fabrics, applying a layer of modified resin adhesive between each layer, and standing at room temperature for 3 to 5 hours to obtain an aramid board; Step D2, hot pressing the aramid plate obtained in step D1 at a temperature of 120° C. for a holding time of 20 seconds, and repeating this process 3 times to obtain a bulletproof back plate.

7. The ultra-wideband electromagnetic shielding and bulletproof composite structural material according to claim 3, characterized in that: The specification of the aramid honeycomb core is 300mmx300mm, a single cell is a regular hexagon, a side length W is 5mm, a thickness W1 is 0.2-0.3mm, and a height h is 10-15mm.

8. The ultra-wideband electromagnetic shielding and bulletproof composite structural material according to claim 4, characterized in that: The carbon fiber cloth is a carbon fiber flat cloth or a woven cloth, and the specification is 300mmx300mm.

9. The ultra-wideband electromagnetic shielding and bulletproof composite structural material according to claim 6, characterized in that: The specification of the aramid non-woven fabric is 300mmx300mm.

10. The method for preparing an ultra-wideband electromagnetic shielding and bulletproof composite structural material according to claim 1, characterized in that: The preparation method is: Step E1, using a modified resin adhesive (5) to sequentially adhere the wave-transmitting skin (1), the aramid honeycomb core (2), the reflector (3), and the bulletproof backboard (4) in a top-down order, wherein the thickness of the modified resin adhesive layer is controlled to be 0.2 to 0.3 mm, thereby obtaining a prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material; Step E2: placing the prefabricated ultra-wideband electromagnetic shielding and bulletproof composite structural material in step E1 in an oven at 120-140° C., and drying for 2-3 hours to obtain the ultra-wideband electromagnetic shielding and bulletproof composite structural material.

Citation Information

Patent Citations

  • Manufacturing process for improving structural strength of wave-absorbing honeycomb sandwich plate

    CN113386449A

  • Lightweight broadband wave-absorbing material for high-power microwave anechoic chamber and preparation method of lightweight broadband wave-absorbing material

    CN113394573A

  • Carbon fiber tube reinforced external self-similar fractal composite electromagnetic shielding honeycomb structure plate

    CN113766820A

Cited By

  • Composite cloth with electromagnetic shielding effect and preparation and application thereof

    CN122275336A